2020
DOI: 10.1136/bmjopen-2020-042867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 lockdown on child protection medical assessments: a retrospective observational study in Birmingham, UK

Abstract: ObjectivesTo determine any change in referral patterns and outcomes in children (0–18) referred for child protection medical examination (CPME) during the COVID-19 pandemic compared with previous years.DesignRetrospective observational study, analysing routinely collected clinical data from CPME reports in a rapid response to the pandemic lockdown.SettingBirmingham Community Healthcare NHS Trust, which provides all routine CPME for Birmingham, England, population 1.1 million including 288 000 children.Particip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 6 publications
0
50
1
Order By: Relevance
“…However, social prescribing link workers were praised for their work, telephoning vulnerable people and navigating their non-medical needs. Concerns around child safeguarding were not unfounded, with a significant reduction in the number of children referred for Child Protection Medical Examinations during the period of the first lockdown [21,22]. A recent report highlighting Child Welfare Inequality shows the unequal distribution of safeguarding interventions across the socioeconomic spectrum and the need for enhanced safeguarding support in deprived communities during and after the pandemic [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, social prescribing link workers were praised for their work, telephoning vulnerable people and navigating their non-medical needs. Concerns around child safeguarding were not unfounded, with a significant reduction in the number of children referred for Child Protection Medical Examinations during the period of the first lockdown [21,22]. A recent report highlighting Child Welfare Inequality shows the unequal distribution of safeguarding interventions across the socioeconomic spectrum and the need for enhanced safeguarding support in deprived communities during and after the pandemic [23].…”
Section: Discussionmentioning
confidence: 99%
“…36 Violence, abuse against children Routinely collected clinical data on Child Protection Medical Examinations (CPME) from Birmingham (UK) showed a significant drop of 39% (95% CI 14% to 57%) in CPME referrals during 2020 compared with previous years, mainly associated with decreased school staff referrals. 37 A study from the US found an increase in the Open access number of children with physical child abuse trauma, 38 and the Florida child abuse allegation data showed a decrease in 27% (n=15 000) in the number of allegations of child abuse and neglect comparing with the same 2 months of 2019 (table 5). 39…”
Section: Diabetes Mellitusmentioning
confidence: 96%
“…Outcome measures Five studies addressed mental health, [19][20][21][22][23] three studies analysed physical activity and obesity, 18 24 25 three studies examined diabetes mellitus, [26][27][28] eight studies approached changes in the access and use of healthcare services, [29][30][31][32][33][34][35][36] while three studies analysed data regarding child abuse and violence. [37][38][39] Mental health One Australian study showed a significant increase in depressive symptoms and anxiety and a significant decrease in life satisfaction during school closure and lockdown, mainly in girls (table 1). 19 A Spanish study gave evidence to a worse total difficulty score of the Strengths and Difficulties Questionnaire according to parent-proxy responses.…”
Section: Study Selection and Risk Of Biasmentioning
confidence: 99%
“…The data show an increase in the number of children exposed to violence and witnessing domestic violence during the pandemic. Whereas, limited school activities and reduced direct contact with primary healthcare may cause a decrease in child abuse victims' identification (39)(40)(41).…”
Section: Mental Health and Development In The Communitymentioning
confidence: 99%